Attacks Directed at Caesar In Cicero’s Paradoxa Stoicorum - Daniela Galli (Ciceroniana On Line, 2023)
Paradoxa Stoicorum is a short essay written by Cicero in 46 BC focused on six Stoic Paradoxa. In this essay Cicero doesn’t limit himself to quoting the Stoic sources: he also applies the Stoic paradoxa to his own Roman world. Therefore, Paradoxa Stoicorum is rich in allusions and references to Cicero’s contemporary Rome. Politics was dominated at that time by the figure of Julius Caesar: in April 46 BC Caesar was appointed dictator for 10 years and the dictatorship granted him near absolute power in both theory and in practice. In 2000 one of the most astute scholars who studied Cicero, Emanuele Narducci, noted that Paradoxa Stoicorum is full of hidden opposition against Caesar’s dominion. Nevertheless, this aspect hasn’t received further study from other scholars. The article examines the most direct attacks to Caesar in Paradoxon 5.